Comparative Study on Phytochemical Composition, Antioxidant, and Anti-HSV-2 Activities of Sambucus nigra L. and Sambucus ebulus L. Extracts - Daniela Seymenska; Kalina Shishkova; Anton Hinkov; Niko Benbassat; Desislava Teneva; Petko Denev (Applied Sciences, 2023)
Sambucus nigra (SN) and Sambucus ebulus (SE) are widely used in folk medicine, primarily as antiviral agents for colds and influenza. In the current study, the antiviral activity of extracts of SN and SE fruits, flowers, and leaves were tested against herpes simplex virus type-2 (HSV-2). The HPLC analysis of the investigated extracts revealed the presence of phenolic acids, flavonoids, and anthocyanins. Rutin and chlorogenic acid were the main polyphenol constituents in flower and leaf extracts, whereas anthocyanins were predominant in fruit extracts. The flower extract of SN was characterized by the highest content of rutin and chlorogenic acid—14,232.1 mg/100 g dry weight (DW) and 7086.7 mg/100 g DW, respectively. SN fruit extract revealed the highest antioxidant activity measured using ORAC and HORAC methods—11,443.1 μmol TE/g and 8198.9 μmol GAE/g, respectively. To evaluate cytotoxicity, antiviral, and virucidal activities against HSV-2, the MTT assay and method of Reed and Muench were used. The least toxic extracts were PSNFrE and PSEFrE. The maximum tolerable concentration (MTC) of PSNFrE was 2000 μg/mL and the calculated CC50 value for that extract was 3570 μg/mL. The inhibitory activity against virus replication was established for three of the extracts—PSNFlE, PSNLE, and PSNFrE. PSEFrE showed neither activity against virus replication, nor virucidal activity. The data suggest a significant inactivation of more than 98% after 60 min of contact of HSV-2 virions with the PSNFrE applied in MTC. The current study provides evidence that Sambucus nigra reveals anti-HSV-2 activity; however, the most active parts of the species were fruits. Therefore, SN fruits and their extracts can be used as an attendant therapy for HSV-2 viral infections.